Ecological and Bioengineering Studies for Stabilizing the Wad Medani-Sennar Roadside Slope Linking the Gezira and Sennar States - Altaeb Mohammed; Xu Wennian; Xia Zhenyao (Advances in Civil Engineering)
The erosion of the highway embankment slope's soil along the Wad Medani-Sennar road is a significant issue, as there are many traffic accidents on this road, with an average of 15 to 25 fatalities per annum. It was thus decided to investigate this issue to find a method to protect slope from erosion on this road and to provide new approaches to slope erosion knowledge gap in Sudan. An engineering survey was carried out, followed by geotechnical studies, experimental work and interviews with academic experts regarding native vegetation in the survey area. These include measuring the eroded parts of the road; studying cross- sections of the road; soil experiments to check the strength, compaction and particle size distribution; and a native vegetation survey to check for suitable plants that could be used to control the slope erosion. It was found that an appropriate bio-engineering method to stabilize the slope soil against erosion due to rainfall was to cultivate the grasses Cynodon Dactylon and Vetiver on the slopes. In conclusion, that using native vegetation for eco -protection, was an excellent solution to the problem based on the climate, native vegetation, and type of soil in Sudan and it reduces the accidents.